Reducing agrochemical use for nature conservation by Italian olive farmers: an evaluation of public and private governance strategies. Issue 1 (2nd January 2018) - Giomi, Tatiyana; Runhaar, Piety; Runhaar, Hens
ABSTRACT: A variety of public policies and private strategies have been implemented to stimulate farmers to implement nature conservation measures. Examples include publicly funded agri-environment schemes (AES) but also eco-labels and Alternative Food Networks; strategies that have been implemented in response to the continuous decline in species abundance and diversity due to agricultural intensification and scale enlargement. Whereas AES as a distinct governance strategy has been evaluated in detail, less is known about other strategies. In this paper, we assess the relative importance of the variety of public and private strategies aimed at enhancing species abundance and diversity in Italian olive farming through a reduction in agrochemical use. In a survey of olive farmers in the region of Tuscany, we found that although farmers are exposed to a variety of public and private strategies, personal motives to reduce agrochemical use are most important. Moreover, having a Corporate Social Responsibility plan or engaging in direct sales to consumers are the only strategies that are related to a reduction in agrochemical use. These findings suggest self-governance is a powerful strategy for enhancing species diversity and abundance in agricultural landscapes. Yet it also means contributing to nature conservation and restoration is a voluntary act. Olive farmers who do not voluntarily contribute to nature conservation by reducing agrochemicals need to be incentivized by show-casing farmers who did reduce their agrochemical use, by critical consumers or by stricter rules in AES or in generic agri-environmental legislation.